Investigation of solution-processed tungsten disulfide as switching layer in flexible resistive memory devices for performance and stability - Shalu Saini; Shree Prakash Tiwari (Nano Express)
Solution-processed tungsten disulfide (WS _2 ) is demonstrated as a promising resistive switching layer for flexible resistive random access memory (RRAM) devices. For this study, WS _2 nanoparticle solution was prepared by liquid exfoliation process from WS _2 powder and comprehensive material investigation was performed to understand the suitability for device fabrication through morphologies and electronic behavior. Devices were fabricated on indium tin oxide (ITO) coated flexible polyethylene terephthalate (PET) with ITO acting as bottom electrode (BE) and silver (Ag) deposited as top electrode (TE) with thin film of WS _2 prepared by spin coating as an active layer between electrodes. These fabricated flexible RRAM devices exhibited resistive switching characteristics with low operating voltages ( V _SET ∼0.5 V and V _RESET ∼−1.4 V) over 100 consecutive cycles, along with impressive retention time of ∼10 ^4 s and high I _ON / I _OFF of ∼10 ^4 . The performance variation of these devices was also investigated upon bending at radii of 12 mm and 5 mm indicating consistent switching, however a decay in LRS was observed after 250 s upon investigation of retention. These findings suggest that solution-processed thin films of WS _2 nanomaterial can act as a promising switching layer for flexible electronics.